Piratería en la Antigüedad : un ensayo sobre historia del Mediterráneo - Ormerod, Henry Arderne, 1886-1964 (Colección Isla de la Tortuga, 2012)
Henry Ormerod's classic Piracy in the Ancient World brings the treachery of the ancient high seas alive. Drawing on the works of Homer and Thucydides and the historical records that have survived from ancient Greece and Rome, Ormerod reconstructs the dangers of coastal living and seafaring and the attempts of ancient society to protect itself against the threat of invasion from the seas. He describes the general nature of early piracy, ancient navigation, and the pirate's routines and tactics.